PRESENT CONSTITUTIONAL STATUS OF AZAD JAMMU & KASHMIR - Muhammad Ashraf Qureshi ASC; Dr. Sadia Tabassum (International Journal of Contemporary Issues in Social Sciences, 2024)
The basic question whether Azad Jammu and Kashmir territory comes within the definition of a State, if yes, then which class of State qualifying under International law and whether its so called Interim Constitution 1974 comes within the definition of a Constitution or not requires a detailed legal and constitutional debate cannot be tackled with herein. However, as per its present constitutional status under the Constitution of Pakistan, India and particularly under its own so called Constitution is in doldrums. This is the main theme of this article, as different courts have different views with regard to the Constitutional status of this disputed territory. There are land marks judgments on it but that too have been given under different circumstances in different way in order to resolve the issue for the time being on biased and personal interest basis, but on permanent basis it is yet to be decided that what is the constitutional status of Azad Jammu and Kashmir and how the people of this area are required to be treated nationally and internationally. For the above purposes, firstly the Azad Jammu and Kashmir’s nature as a whole have been discussed under the first heading. Then the nature of the so called constitution of Azad Jammu and Kashmir have been discussed particularly comparing it with Gilgat Baltastan’s territory and the status of its people under the land marks judgments of the Supreme Court of Pakistan. Then under different headings the constitutional status of Azad Jammu and Kashmir have been discussed under Indian Constitution and Pakistan Constitution comparatively. For this purpose, different land mark case laws of the superior courts have been taken into consideration.